دراسة التمغنط الموجه للرسوبيات الاصطناعية، وتصحيح خطأ ميله - محمد لؤي (Latakia University Journal -Basic Sciences Series, 2018)
ترتكز دراسة الخواص الفيزيائية لعلوم الأرض إلى فهم طبيعة وخواص مغناطيسية الصخور )التمغنط الموجه للرسوبيات، والتمغنط الحراري للصخور النارية( لعدة أسباب منها: (1 إن مركبة التمغنط الموجه والحراري للصخور الرسوبية والنارية، على الترتيب، تحتفظ بقيمة ثابتة باتجاه الحقل المغناطيسي الأرضي، محافظة على هذا الاتجاه المكتسب ملايين السنين بعد تصلبها. (2 تسمح لنا دراسة مغناطيسية الصخور بفهم البنية الداخلية للأرض من خلال معرفة الفلزات الموجودة في الصخور. (3 تعتمد عملية التنقيب المغناطيسي عن الثروات المعدنية في باطن الأرض على دراسة مركبة التمغنط الموجه؛ إذ يرتبط الشواذ المغناطيسي بشكل خاص بالصخور الحاوية على بعض المواد المغناطيسية. يهدف هذا البحث إلى دراسة الخصائص الفيزيائية للتمغنط الموجه للرسوبيات الاصطناعية ذات أحواض ترسيبية كبيرة المساحة بغية تقريب الدراسة من الظروف الطبيعية لتشكل الصخور الرسوبية. Physical properties in geology are based on understanding the nature and characteristics of rock magnetism (guided and thermal magnetism of sedimentary and igneous rocks) for several reasons, namely: 1. The component of oriented and thermal magnetism of sedimentary and igneous rocks maintains a fixed value in the direction of the ground magnetic field. 2. A study of rock magnetism allows us to understand the internal structure of the earth by identifying the minerals present in rocks. 3. The magnetic excavation of mineral resources in the depth of earth depends on studying the component of guided magnetism, where magnetic abnormality is specially connected with rocks containing some magnetic materials. This research aims at studying the physical properties of guided magnetism for artificial sediments whose area of sedimentary basins are so big in order to approach this study from the natural conditions responsible for forming sedimentary rocks.